Corporate Social Responsibility and the Sustainable Development Goals: A Case Study of Nusantara, The Future Capital City of Indonesia - Fajri, Choirul; Sari, Norma; Amali, Muhammad Thoyib (Journal of Ecohumanism, 2024)
Corporate Social Responsibility (CSR) is a company’s commitment to provide benefits to society. CSR programs are closely related to achieving Sustainable Development Goals (SDGs). Where companies can integrate programs based on SDGs achievement indicators. The Indonesian government is focusing on developing Nusantara, the future capital city in East Kalimantan Province. The Indonesian government is trying to increase investment from numerous parties in this development. One of the expected investments is through CSR programs implemented by various companies. This research aims to analyze the implementation of CSR programs to encourage the achievement of SDGs in Nusantara. This research used a qualitative approach with a case study method. Data collection techniques were conducted through in-depth interviews, observations, and focus group discussions. This research shows that many companies have implemented CSR programs at Nusantara, and there have been efforts to encourage the achievement of the SDGs. However, this cannot be separated from various challenges, such as the absence of specific regional government regulations and differences in interests between the government, companies, and the community. Communication is an important aspect to bridge this problem. Cooperation and collaboration with various parties are also expected to support sustainable development in Nusantara.